The role of phytochrome B1 of tomato (Solanum lycopersicum L.) in the reproductive stage during drought stress - Silva Junior, Carlos Alberto [UNESP] (Universidade Estadual Paulista (Unesp), 2021)
Photoreceptors are primarily known as key photomorphogenic modulators of various physiological events during plant development. Although there are different groups of photoreceptors, the phytochrome B (phyB) family mediates developmental responses in a wide range of plant species, from seed germination to flowering. In addition, these molecules also regulate abiotic stress acclimation responses, such as salinity, drought, low/high temperature, high light, and heavy metals. The signalling pathways mediated by phyB could enhance plant resistance to environmental stresses, as phyB mutants reduced leaf transpiration through lowering of stomatal conductance, increased the antioxidant system, enhanced protective pigments, and increased the expression of genes related to plant stress acclimation. Therefore, the scope of chapter one is to compile and discuss the evidence on abiotic stress response in plants that are modulated by the phytochrome type B family. In addition, chapter two aimed to elucidate the responses mediated by phyB1 in tomato fruit production comparing the effects of drought stress in vegetative and reproductive stages. The water deficit treatment was performed in two different stages growth: in vegetative (start at 26 days after sowing [DAS]); end at 36 DAS) and reproductive (start at 33 DAS; end at 41 DAS) stage growth.

Os fotorreceptores são conhecidos principalmente como moduladores fotomorfogênicos essenciais de vários eventos fisiológicos durante o desenvolvimento da planta. Embora existam diferentes grupos de fotorreceptores, a família do fitocromo B (phyB) medeia as respostas de desenvolvimento em uma ampla gama de espécies de plantas, desde a germinação de sementes até a floração. Além disso, essas moléculas também regulam as respostas de aclimatação ao estresse abiótico, como salinidade, seca, temperatura baixa / alta, luz alta e metais pesados. As vias de sinalização mediadas por phyB podem aumentar a resistência da planta a estresses ambientais, pois os mutantes de phyB reduzem a transpiração foliar por meio da redução da condutância estomática, aumentam o sistema antioxidante, aumentam os pigmentos protetores e aumentam a expressão de genes relacionados à aclimatação ao estresse das plantas. Portanto, o escopo do capítulo um é compilar e discutir as evidências sobre a resposta ao estresse abiótico em plantas que são moduladas pela família do fitocromo tipo B. Além disso, o capítulo dois teve como objetivo elucidar as respostas mediadas por phyB1 na produção de frutos de tomate, comparando os efeitos do estresse hídrico nos estágios vegetativo e reprodutivo. O tratamento da deficiência hídrica foi realizado em dois estágios distintos de crescimento: no vegetativo (início aos 26 dias após a semeadura [DAS]); termina aos 36 DAS) e reprodutivo (começa aos 33 DAS; termina aos 41 DAS) estágios de crescimento.
O papel do fitocromo B1 de tomate (Solanum lycopersicum L.) na fase reprodutiva durante o deficit hídrico
Keywords: Physiology; Cultures; Fruit